#Blessed: the moderating effect of dispositional gratitude on the relationship between social comparison and envy on Instagram - Kaminger, Stella; Roth, Leopold Helmut Otto; Laireiter, Anton-Rupert (Frontiers in Psychology, 2023)
Introduction The role of dispositional gratitude as a positive psychological resource and prosocial personality trait in real life interactions militates in favor of its introduction to the research field of social media. Methods Based on a literature review of the previously studied relationship of dispositional gratitude with social comparison and envy in offline settings, a twofold moderation model was proposed and quantitatively tested in a cross-sectional sample of N = 268 Instagram users aged between 18 and 40 years. Additionally, the dual conceptualization of benign and malicious envy was scrutinized by validating its respective connections with affective outcomes and inspiration on Instagram. Results and discussion Dispositional gratitude serves as a protective factor when using Instagram by significantly mitigating the relationship of social comparison and malicious as well as general envy on Instagram. Furthermore, the results support the more nuanced understanding of envy as a dual construct in the face of social media use.